Genome-wide identification and expression analysis of asparagine synthetase family in apple - Xi-sen YUAN; Zi-peng YU; Lin LIU; Yang XU; Lei ZHANG; De-guo HAN; Shi-zhong ZHANG (Journal of Integrative Agriculture, 2020)
Asparagine is an efficient nitrogen transport and storage carrier. Asparagine synthesis occurs by the amination of aspartate which is catalyzed by asparagine synthetase (ASN) in plants. Complete genome-wide analysis and classifications of the ASN gene family have recently been reported in different plants. However, systematic analysis and expression profiles of these genes have not been performed in apple (Malus domestica). Here, a comprehensive bioinformatics approach was applied to identify MdASNs in apple. Then, plant phylogenetic tree, chromosome location, conserved protein motif, gene structure, and expression pattern of MdASNs were analyzed. Five members were identified and distributed on 4 chromosomes with conserved GATase-7 and ASN domains. Expression analysis indicated that all MdASNs mRNA accumulated at the highest level in reproductive organs, namely flowers or fruits, which may be associated with the redistribution of free amino acids in plant metabolic organs and reservoirs. Additionally, most of MdASNs were dramatically up-regulated under various nitrogen supplies, especially in the aboveground part. Taken together, MdASNs may be assigned to be responsible for the nitrogen metabolism and asparagine synthesis in apple.